An analysis of the indoor air quality of selected areas in the university health service a case study - Aman, Isis A.; Gallardo, Mildred; University of the Philippines. University Health Service (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
This study focused on analyzing the effect of the current design of the University of the Philippines Health Service on the indoor air quality on the selected areas of the said facility which include the Nursing Department, the Medical Laboratory Department, the Administrative Department, and the Public Health Unit. The exploratory case study involved the participation of 26 staff members from four departments in a self administered survey an interview with the Acting Director to find out about the facility information and maintenance protocols observation to assess the conditions of the selected interior spaces including the ventilation system, existing finishes and layout and consultation with an Environmental and Occupational Health specialist to analyze how the current indoor air quality affected the health and well being of the respondents. Survey results showed symptoms experienced by respondents including frequent colds or runny nose 15 respondents, headaches 9 respondents, burning or itchy eyes 9 respondents, frequent cough 9 respondents, frequent sneezing 9 respondents and fatigue or drowsiness 8 respondents. Chronic medical conditions such as allergies, asthma, sinusitis, bronchitis and conjunctivitis were also indicated by 14 out of 26 respondents. It was observed that overcrowding, presence of areas of stagnation, inadequate space allocation and unsustainable maintenance practices were factors that have contributed to poor indoor air quality of the facility. Interior design strategies in proper planning, collaboration with allied professionals and specialists, and adaptation of sustainable maintenance practices may be looked into for possible future renovations to address the indoor air quality concerns of the facility.
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Hospital buildings -- Heating and ventilation -- Philippines